Fracture Resistance of Resin Matrix Ceramic Post and Core Compared to Prefabricated Fiber-Reinforced Composite Post and Core in Non-Ferrule Effect Teeth: An InVitro Study - Kunawongkrit, Keeratikarn; Mahardawi, Basel; Nan, Pheeradej Na; Laoharungpisit, Palawat; Ratanakupt, Kwanchanok; Aimjirakul, Napapa (European Journal of Dentistry, 2025)
This research studies the fracture resistance of a non-ferrule endodontically treated tooth restored with two types of resin matrix ceramic (Enamic and Cerasmart) post and core compared with the conventional prefabricated fiber-reinforced composite (FRC) post and core.Thirty single-root-canal premolars were sectioned to 13 mm root length and then all the roots were filled, using a crown-down technique for root canal preparation and one cone technique for root canal obturation, All the roots were randomly divided into three groups (n = 10) according to post and core material; (1) Enamic group (EN), (2) Cerasmart group (CM), and (3) prefabricated fiber post group (FRC). Three groups of specimens were tested using a universal testing machine (EZ Test Series, Shimadzu, Japan). Specimen blocks were fixed into a holder with an inclination of 45 degrees. The force was loaded to a palatal incline of buccal cusp at a crosshead speed of 0.5 mm/minute until there was split or fracture of the tooth. The maximum braking force was recorded in Newton (N), and the mode of failure was observed by a stereomicroscope.The dependent variable was fracture resistance (maximum breaking force) and the data were analyzed using one-way analysis of variance and then multiple comparison Tukey's tests were used, aiming to find means that are significantly different among the groups. Moreover, the failure mode was analyzed using the chi-square test.A significant difference was recorded. Teeth restored with prefabricated FRC had the most fracture resistance 342.19 ± 79.34 N (p = 0.007), followed by the resin matrix ceramic group (265.10 ± 48.58 N: Cerasmart) and Enamic group (260.98 ± 43.96 N: Enamic). No significant difference between the Enamic and Cerasmart groups was noted. Additionally, no significant difference in the mode of failure was recorded among the three groups.The fracture resistance of a non-ferrule endodontically treated tooth restored with the conventional prefabricated FRC post and core is greater than that restored with either type of resin matrix ceramic (Enamic and Cerasmart). This explains the higher failure rate resulting from the use of resin matrix ceramics.
Keywords: ceramic; invitro technique; post and core; resin matrix